Legislation as a pratical instrument in sustainability - Veríssimo Chaves Guimarães, Samara (AESOP, 2016)
The aim of this paper is, after doing a reflection about the concept, to bring a brief overview of Brazilian law that after the 1980s, employ in their content terms like sustainability and sustainable development, in order to reassert the role of these laws in the construction of cities in consonance with sustainable principles. In this sense, much is still discussed about overcrowded cities, which caused serious environmental problems as a result of the occupation of inappropriate areas, destruction of ecologically valuable resources and environmental pollution. The processes of massive immigration from the countryside to metropolises eventually externalize social and environmental costs in the form of saturation of air pollution levels, water, noise and visual. The urban environment, according to Mota (2011), consists of the "natural system" and the "anthropic system" and changes made by man in the environment are always made quickly and intensely and does not allow it to have a normal recovery of nature, whose processes occur more slowly. The search for the "relative balance" in the ecosystem, according to the author, is the biggest challenge; how to achieve sustainable development of cities in a way that achieves balance between human intervention and conservation of natural resources. Although Engels (1845) had already pointed out the factors of environmental degradation that existed in the nineteenth century working class neighborhoods1, it was only in the twentieth century, when the "environmental crisis" hit the interests of the bourgeoisie that this speech has gained relevance in the media, in academia and public opinion (Coutinho, 2004).
Proceedings of the IV World Planning Schools Congress, July 3-8th, 2016 : Global crisis, planning and challenges to spatial justice in the north and in the south